Effectiveness of Applying Anti-Aging Cream with Lemon Peel Extract (Citrus Limon) in Inhibiting the Skin Aging Process of Wistar Rats (Rattus Norvegicus) Exposed to Ultra Violet-B Rays - Sifa Nurlatipah; Yeni Halim; Robby Gunawan Sebayang (CV. Inara, 2023)
Aging is a gradual physiological change in an organism that results in senescence or a reduction in biological function and the ability of the organism to respond to metabolic stress. Aging occurs in cells, organs, or the entire organism over time; the study of the aging process seeks to understand and regulate all elements that contribute to an individual's life constraints. The predominant acute consequence of UV radiation on normal human skin is sunburn-induced inflammation (erythema). The overall goal of this study is to examine and test the efficacy of applying an anti-aging cream containing lemon peel extract (Citrus limon) in preventing the aging process of mouse skin. Wistar strain (Rattus norvegicus) exposed to ultraviolet-B light. The specific goal of this study is to investigate the efficacy of applying lemon peel extract (Citrus limon) cream at 5%, 10%, and 15% concentrations in preventing the aging process of rat skin exposed to UV-B radiation.